Glucose metabolism in obese and lean adolescents with polycystic ovary syndrome - Preamrudee Poomthavorn (2018)
Data on glucose metabolism in Asian adolescents with polycystic ovary syndrome (PCOS) are limited. Glucose metabolism assessment using an oral glucose tolerance test (OGTT) in obese and lean Thai adolescents with PCOS, and a comparison between the two groups were done. Thirty-one patients (19 obese, 12 lean) were enrolled. Their median (range) age was 14.9 (11.0 - 21.0) years. Eighteen patients had abnormal glucose metabolism (13 hyperinsulinemia, 4 impaired glucose tolerance, and 1 diabetes). Compared between obese [median (range) BMI Z-score, 1.6 (1.2 - 2.6)] and lean [median (range) BMI Z-score, 0.1 ( - 1.4 to 0.6)] patients, the frequencies of each abnormal OGTT category, areas under the curves of glucose and insulin levels, and insulinogenic index were not different; however, insulin resistance was greater in the obese group. In conclusion, a high proportion of our adolescents with PCOS had abnormal glucose metabolism. Therefore, OGTT should be performed in adolescents with PCOS for the early detection of abnormal glucose metabolism.